WATER CONSUMPTION, WATER USE EFFICIENCY AND POTATO YIELD UNDER THE INFLUENCE OF MOISTUER DEPLETION AND ADDITION METHOD - Mustafa S. A. A (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Field experiment was conducted at AL Ramadi – Anbar province in western Iraq. far fall season 2020 in sandy clay loam soil which has 58.90 gm Kg -1 gypsum, to study the effect of water depletion, addition method in water consumption and water use efficiency. Irrigation was at depletion rates 40, 50 and 60% of available irrigation water, with three ways: Complete addition of irrigation depth, half addition included adding half of irrigation depth and adding another half after 6 hours, third addition division to three parts at duration of 6 hours, treatments distributed according spilt plot design in RCBD with three replicates. Potato planted in 13.09.2020. Evaporation pan Class A used to scheduling the irrigation. Water consumption calculated by equivalent it of added water depth. Results showed increasing in water consumptive with decreasing in depletion rate, highest value of water consumptive reached 324.13 mm at 40% depletion of available water, while decreased to 293.61 mm at 60% depletion with decreasing rate reached 9.41 %, Total yield rate prevailed at 40% depletion of water available which reached 22.73 t h -1, Also total yield and water use efficiency prevailed significantly at triple addition which reached 23.90 t h -1, 14.17 kg m-3 respectively.